Knowledge Flows and R&D Co-operation: Firm-level Evidence from Germany - Tobias Schmidt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
This paper analyzes the determinants of R&D co-operation among German manufacturing firms. Using firm level data from the Third Community Innovation Survey from Germany, we focus on the role of spillovers in explaining R&D cooperation. We also investigate firms? decisions to cooperate with research institutions or with suppliers and customers. Implementing a two-step estimation procedure, we find a positive effect of knowledge flows on the probability of R&D co-operation in most model specifications. Additionally, we show that firms with high intramural R&D budgets are more likely to cooperate with universities and research institutions than with suppliers and customers.
More recent version: http://hdl.handle.net/10419/24164
Keywords: O31; L22; O32; 330; Spillovers; R&D Co-operation; CIS 3; Industrielle Forschung; Forschungskooperation; Wissenstransfer; Spillover-Effekt; Deutschland